EFFECT OF WATER POLLUTION ON HISTOPATOLOGY FISH GILL: LITERATURE REVIEW - Riri Putri Arianti; Yusni Atifah; Vauzia (Jurnal Serambi Biologi, 2023)
Water pollution is a deviation of the properties of water from normal conditions. Water that is polluted by pesticide residues when it has reached a certain concentration will greatly affect the environment and the aquatic organisms that live in it. Fish is one of the aquatic biota that can be used as an indicator of the level of pollution that occurs in the waters. Fish that have been contaminated with contaminants such as hazardous materials for a long time will experience changes in structure or function and will also experience changes in histological conditions. Therefore, any changes that occur in the aquatic environment will directly or indirectly affect the gills both structurally and functionally. This type of research is research that uses the literature review method. The stages of literature collection used in this study refer to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. This stage consists of four procedures, namely, identification, screening, eligibility and acceptance. This study shows that water pollution greatly affects the histopathology of fish gills because it can cause several disorders and diseases of fish gills. Key words : Water Pollution, Fish, histopathology of fish gills